Macrosurfactant-mediated, aminopolycarboxy-acid-decorated open-cellular adsorbent for removing metal micropollutants from water. (12th February 2020) - Weng, Shiqi; Jin, Ming; Wan, Decheng
Abstract : An open-cellular macroporous monolith with its pore surfaces decorated with aminopolycarboxy acids can be prepared in one pot and used to eliminate trace heavy metal ions in water. Abstract : Aminopolycarboxy acids (APAs) are well known for their ultrastong affinity for heavy metals. Their monolayer, full-coverage, robust and one-step decoration of the surface of a macroporous adsorbent has not yet been realized. In the current work, we derived a cost-effective strategy to produce a porous adsorbent with the aid of a dendritic macrosurfactant. Branched polyethylenimine (PEI) was partly alkylated with glycidyl cetylether (C16) to form a dendritic polyamine macrosurfactant (PEI@C16, M n ∼ 10 4 ). This macrosurfactant well stabilized a water-in-oil high internal phase emulsion (HIPE), while a macrosurfactant counterpart based on linear PEI did so poorly. Heating the HIPE system triggered a simultaneous transformation of the residual amines of PEI@C16 into APAs and of the oil phase (consisting of styrene, divinylbenzene and radical initiator) into an open-cellular solid matrix. The resulting open-cellular monolith showed a rather large specific surface area and very high affinity for various heavy metal ions in water. The adsorption of Pb(ii ) was indicated to follow a chemical and monolayer adsorption mechanism. The adsorbent showed good recyclability, due to the robustly anchored APAs.